Mersalyl: a Diuretic with Antiviral Properties - Kramer, M. J. (1975)
Mersalyl (Salyrgan), an organic mercurial diuretic, was tested against human and animal viruses with in vivo model infections in mice and tissue culture systems. Mersalyl was active against coxsackieviruses A21 and B1 in mice if administered intraperitoneally immediately after infection. No effect was observed if intraperitoneal treatment was delayed 1 or 2 h postinfection, or if treatment was administered either subcutaneously or per os. Topical treatment with a 5% aqueous solution of mersalyl produced a statistically significant effect against herpes simplex dermatitis in mice but the substance was inactive against systemic infections in mice with herpes simplex as well as Columbia SK, influenza, Semliki Forest, and Sendai viruses. Contact inactivation of coxsackieviruses A21 and B1 and herpes simplex virus was observed, but mersalyl was inactive in tissue culture against coxackieviruses A21 and B1, herpes simplex, influenza, rhinovirus, Semliki Forest, Sendai, and vaccinia viruses.